Cyberbullying Discovery on Social Networks: A Study - Sireesha, G; Kranthikumar, G (International Journal of Computer Sciences and Engineering, 2025)
The fast improvement of relational cooperation is upgrading the development of advanced tormenting works out. Most of the general population connected with these activities have a place with the more energetic ages, especially youngsters who are the most exceedingly terrible circumstance are at more risk of pointless undertakings we propose a fruitful predator and harmed singular ID with semantic enhanced thought little of de-noising auto-encoder approach to manage distinguish advanced tormenting message from online life through the measuring plan of a component of decision. We present a graph model to expel the cyberbullying framework, which is used to perceive the most unique cyberbullying predators and abused individuals to situating counts the present channels generally work with the clear catchphrase look moreover, can't grasp the semantic noteworthiness of the substance. So we propose Semantic-Enhanced Marginalized De-noising Auto-Encoder. (smSDA) is created by methods for a semantic development of the notable significant learning model stack de-noising autoencoder. The semantic expansion includes semantic dropout clatter and sparsely necessities, where the semantic dropout bustle is organized in perspective of zone data and the word embeddings framework. The test demonstrates practical of our strategy.